2020
DOI: 10.3390/molecules25061278
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of α-Glucosidase Inhibitory Triterpenoids in Psidium guajava Using HPLC–DAD–ELSD and Pressurized Liquid Extraction

Abstract: Psidium guajava, a popular food and medicine dual purposes plant cultivated in tropical and subtropical regions, has been widely used as food crop and folk medicine, such as anti-diabetes agent, around the world. Triterpenoids have been considered as the major active ingredients of P. guajava. In the present study, a high-performance liquid chromatography coupled with diode array and evaporative light scattering detectors (HPLC–DAD–ELSD) method was developed for simultaneous determination of nine triterpenoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…CA was identified as the most abundant triterpenoid in TGL. Our result was in agreement with a previously reported study on the major triterpenoids in guava leaves . Previous studies, including our group work, has reported that GUB is the major phenolic component present in guava. , The HPLC–DAD-MS analysis revealed that most phenolics including guavinoside B, flavonoids, and oleuropeic acid-conjugated phenolic glycosides in guava leaves were successfully removed from TGL (see Supporting Information Figure S4).…”
Section: Resultssupporting
confidence: 92%
“…CA was identified as the most abundant triterpenoid in TGL. Our result was in agreement with a previously reported study on the major triterpenoids in guava leaves . Previous studies, including our group work, has reported that GUB is the major phenolic component present in guava. , The HPLC–DAD-MS analysis revealed that most phenolics including guavinoside B, flavonoids, and oleuropeic acid-conjugated phenolic glycosides in guava leaves were successfully removed from TGL (see Supporting Information Figure S4).…”
Section: Resultssupporting
confidence: 92%
“…Taking a different administration route, scientists devised nanofiber patches for the transdermal delivery of curcumin. The transdermal route has gained recognition as an alternative to conventional oral delivery for various drugs, with numerous studies indicating improved bioavailability via this route [64][65][66][67][68][69][70][71][72][73]. These nanofibers were created using polyvinyl alcohol and gelation, resulting in a formulation characterized by fiber diameters of 200-250 nm and high reproducibility [74][75][76][77][78].…”
Section: Drug Delivery Approaches For Bioactive Compounds In the Trea...mentioning
confidence: 99%
“…Diversos triterpenos e esteroides foram identificados em derivados da espécie P. guajava, incluindo ácidos ursólico e oleanólico e 20-hidroxi-derivados, ácidos crataegoico, jacumárico, crataególico, guajanoico, asiático, guavacumárico, goreishico, isoneruicumárico, guavênico e guaijavólico, ilelatifol D, uvaol e β-sitosterol e seu glicosídeo (2,5,27,(183)(184)(185)(186)(187)(188). Os meroterpenoides floroglucinol policíclicos guajamer A-H, psidial D-G, um meroterpenoide benzoilfloroglucinol metilado guajamer I, e dois análogos foram isolados das folhas da espécie vegetal (189)(190)(191).…”
Section: Droga Vegetal (Folhas)unclassified